DEVELOPMENT COOPERATION IN DEVELOPING COUNTRIES: A CASE STUDY OF IMPLEMENTATION OF THE INDONESIA-CHINA PROJECT COOPERATION IN THE JAKARTA-BANDUNG HIGH-SPEED RAILWAY DEVELOPMENT - Mahardika, Bagus; Purnawarman, Andi (Jurnal Multidisipliner Bharasumba, 2025)
This study aims to understand and describe the project implementation of Indonesia-China project cooperation in the Jakarta -Bandung highspeed railway development. Data use in this research is secondary and collected using a literature review technique and analyzed qualitatively based on their relevance to the research problem. The result of this study is that the Jakarta-Bandung High-Speed Railway project has been effectively implemented through a functional partnership by Indonesia as host country and China. PT KCIC, a joint consortium between the two countries, was established to manage funding, distribute financing, and serve as the executor of Engineering, Procurement, and Construction (EPC) as well as Operation and Maintenance (O&M). The project reflects mutual interdependence which are China provides expertise, technology, and training to support localization and knowledge transfer, while Indonesia contributes its land and is responsible in the future for regional development along the rail corridor.